Improving Understanding of KPK and FPB Concepts through the Use of PAKABE Teaching Aids in Mathematics Learning - Nurohman, Nurohman; Wasino, Wasino; Handoyo, Eko (Peneliti.net, 2025)
This study investigates the effectiveness of PAKABE (KPK and FPB Boards) as a teaching aid in enhancing elementary students' understanding of mathematical concepts, particularly the Least Common Multiple (LCM) and Greatest Common Factor (GCF). Employing a quasi-experimental design with a pretest-posttest control group, the research involved Grade V students from SD Negeri Gunungtajem. The experimental group received instruction using PAKABE integrated with a Project-Based Learning (PJBL) approach, while the control group was taught using conventional methods. Data were collected through written tests, observation sheets, student response questionnaires, and documentation. Results indicated a significant improvement in the experimental group's learning outcomes, with the number of students meeting the Achievement Level Completeness Criteria (KKTP) increasing from 6 to 14. Students also responded positively to the use of PAKABE, demonstrating increased motivation and engagement. These findings highlight the potential of contextual and interactive teaching aids to improve conceptual understanding and student participation in mathematics learning.